Challenges in dealing with effeminate clients: recommendations for increasing counselors’ competency - Syed Mahmood, Syarifah Rohaniah; Ssekamanya, Siraje Abdallah (2013)
A phenomenological method of qualitative inquiry was used to understand the challenges experienced by Muslim counselors in dealing with Muslim effeminate clients. Interviews were conducted with five counsellors who are Muslims, have basic knowledge of counselling ethics, and have experiences in working with Muslim effeminate clients. As none of them received specific training in dealing with effeminate clients, they experience challenges in dealing with them. Considering the growing numbers of clients with sexual identity issues, this paper recommends strategies to increase counselors’ competency in dealing with effeminate clients.